Optimization of postweld tempering pulse parameters for maximum load bearing and failure energy absorption in dual phase (DP590) steel resistance spot welds - Soomro, I.A. (Elsevier Ltd, 2021)
Resistance spot welds of dual phase (DP) steels are prone to low fracture toughness due to the formation of brittle martensitic structure in the fusion zone (FZ). In-process tempering of martensite via applying second pulse current is considered a new pathway to improve mechanical performance of the welds. The success of in-process tempering depends upon precise controlling the amount of heat input and uniform temperature distribution which in turn influenced by postweld tempering pulse parameters. This paper aims to investigate the effect of three postweld tempering pulse parameters such as welding current, welding time and cooling time applied after main pulse current on microstructure and mechanical properties of DP590 steel resistance spot weld. Mechanical properties in terms of peak load and failure energy were determined after performing cross tension (CT) test. Taguchi quality design based on L16 orthogonal array has been used to determine the optimum conditions for maximum peak load and failure energy. Moreover, microstructure-property relationship is also studied. The results show that at optimum conditions maximum improvement of 62 in peak load and 62.3 in failure energy is achieved in double pulse welds compared with conventional single pulse weld. It was found that improvement in peak load and failure energy resulted from (i) enhanced weld nugget size (WNS) and (ii) tempering of martensite in FZ and heat affected zone (HAZ). These factors are influenced by heat input (Q) during postweld heating cycle (PWHC) which in turn increased with increasing second pulse current and time. Â© 2020 Elsevier B.V.